Structure of Rural Income in Pakistan: Some Preliminary Estimates (The Pakistan Development Review, 1985)
The main objective of this paper is to study the rural income distribution in Pakistan by determining income accruing to farm and non-farm households from various assets held by them. Most of the existing literature on income distribution in Pakistan [3; 4; 8; 10; 12; 14; 17] focuses either on aggregate income or only on income from crops and classifies rural households by their income level. It ignores the internal structure of income as well as one of the main distinguishing features of rural households, namely their relation to land. In a developing country, however, the internal structure of income is likely to change with changes in the level of income. It is therefore important to assess the contribution of an individual factor (asset) to the overall income of a household and its impact on income inequality. Moreover in the case of Pakistan where land is becoming increasingly scarce for small farmers [7; II] it should be interesting to know how these farmers are trying to "fight back" the pressure on their land with alternative sources of income.